Faktor-Faktor Penyebab Terjadinya Pernikahan Usia Dini di Desa Pelat Kecamatan Unter Iwes Sumbawa Besar - Lina Safitri (LPPM STIKES Griya Husada Sumbawa, 2021)
The purpose of this study is to determine the knowledge factor, economic factor, trust factor, mass media or information factor, promiscuity factor, and health service availability factor that causes early marriage in Pelat Village, UnterIwes District. This research is an exploratory, descriptive study with a cross-sectional approach. The population in this study was 130 people, and the number of samples was 57 people by purposive sampling. Data collection techniques in this study used interview techniques, filling out questionnaires, and literature studies. The analytical test used is a descriptive analysis of percentage and univariate. The results showed that 39 respondents (68%) married with good knowledge, and 18 respondents (32%) married with less knowledge. Almost 14 respondents (25%) chose to do early marry because of economic factors, and 43 respondents (75%) married not economic factors. Therefore, 17 respondents ( 30%) answered to do early married because of their beliefs and 40 respondents (70%) not causing the beliefs factor. Then, 40 respondents (70%) married because mass media and information influenced them, 17 respondents (30%) married because they were not affected by mass media and news. Then, 42 respondents (74%) married due to the negative impact, 15 respondents (26%) married because of the positive impact. Lastly, 49 respondents (86%) had received health information, and 8 respondents (14%) did not receive health information use of mass media in their teenagers. Teenagers are more concerned about socializing, so they must be wise in using mass media under their parent's control.